(untitled) (Journal of Asian Development Studies, 2025)
The study sheds light on the effectiveness of the integrated instructional tools on prospective teachers. The incorporation of instructional proficiency in teaching has revolutionised teacher education, and the use of innovative approaches in teaching methodology has changed the teaching-learning process. The mixed-methods research study examines the use and perception of instructional tools among prospective teachers at universities. To determine the impact of technology on the teacher education system, purposive sampling was employed. The mixed design was incorporated. Qualitative sampling was conducted through interviews and focused group discussions, while quantitative sampling was conducted using questionnaires. Qualitative data were analysed using thematic analysis to identify patterns, themes, and insights that emerged from the data. Descriptive statistics and inferential statistics were used to analyse the survey data and identify significant trends and correlations. The sample consisted of prospective teachers and teacher educators. Participants’ opinions of instructional tools, especially Kahoot, Nearpod, and Google Sites, were largely positive, as indicated by descriptive statistics, and the survey demonstrated good reliability (Cronbach’s Alpha = .935). Individual characteristics may influence how aspiring teachers assess technology in the classroom, according to a one-way ANOVA that found significant differences in perceptions of how effective technology is at enhancing academic accomplishment, teaching proficiency, and student learning outcomes (p< .05). The research provides valuable insights into how teacher education programs can effectively integrate instructional technology and prepare prospective teachers for the changing paradigm of education.